1996
DOI: 10.1017/s0021859600074864
|View full text |Cite
|
Sign up to set email alerts
|

Growth, development and yield of bambara groundnut (Vigna subterranea) in response to soil moisture

Abstract: SUMMARYStands of bambara groundnut (Vigna subterranea (L.) Verde.) were grown in five controlledenvironment glasshouses at the Tropical Crops Research Unit, University of Nottingham, Sutton Bonington Campus, in 1990. Five soil moisture regimes were imposed (one per house), from fully irrigated each week (treatment A), to no irrigation after crop establishment at 35 days after sowing (DAS) (treatment E). Decreasing the amount of water applied resulted in a decline in total dry matter production and harvest inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 14 publications
3
46
0
2
Order By: Relevance
“…We used seed of landraces from the local market in our study. It is striking that Bambara groundnut performed so poorly in the two dry seasons (2002/03 and 2004/05), yet Collinson et al (1996) suggested that Bambara groundnut is resistant to drought stress. Studies of the crop under semi-arid conditions in Botswana reported high grain yields of 0.4 to 1.5 t ha −1 (Karikari and Tabona 2004), though the crop was irrigated at emergence.…”
Section: Seasonal Rainfallmentioning
confidence: 99%
“…We used seed of landraces from the local market in our study. It is striking that Bambara groundnut performed so poorly in the two dry seasons (2002/03 and 2004/05), yet Collinson et al (1996) suggested that Bambara groundnut is resistant to drought stress. Studies of the crop under semi-arid conditions in Botswana reported high grain yields of 0.4 to 1.5 t ha −1 (Karikari and Tabona 2004), though the crop was irrigated at emergence.…”
Section: Seasonal Rainfallmentioning
confidence: 99%
“…The desirable agronomic traits of Bambara groundnut such as yield potential (Berchie et al 2010;BAMFOOD 2012), nutritional composition (Brough and Azam-Ali 1992;Brough et al 1993) drought tolerance and adaptations to marginal soils (Collinson et al 1996;Mwale et al 2007a, b), N-fixation and soil fertility improvement (Kishinevsky et al 1996;Dakora 1998;Herridge and Rose 2000;Herridge et al 2008;Mohale et al 2013) have been documented. The crop largely exists as landraces with few varieties developed through controlled breeding (Massawe et al 2002;Basu et al 2007b;Massawe et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Water stress occurring at any stage can have a negative impact on yield. Several studies described the germination, growth and yield responses of bambara groundnut landraces to water stress (Collinson et al 1996, 1997, 1999, Sesay et al 2004, Mwale et al 2007, Vurayai et al 2011a, 2011b, Berchie et al 2012), but information describing local bambara groundnut landraces is scarce. Collinson et al (1997) reported that drought tolerance in a Zimbabwean cream bambara groundnut landrace was the result of an ability to maintain leaf turgor pressure through a combination of osmotic adjustment, reduction in leaf area and effective stomatal control.…”
mentioning
confidence: 99%